Introducing Communication Skills Teaching into the Curriculum - Murtaza Gondal , Sumera Mushtaq , Amir Shahzad , Zareen Zaidi , Shaheen Moin , Ahsan Mukhtar Gillani, (Journal of Rawalpindi Medical College, 2011)
communication skills workshop for final year medical students. Methods: A simple observational pre-post workshop analysis was done after a 2 day Communication Skills workshop which included four themes: doctor-patient relationship-building skills, breaking bad news, dealing with distressed patients and patients with psychosocial issues, conflict resolution and negotiation skills. At the end of the workshop an OSCE was conducted, using in-house videos, and trainee doctors acting as simulated patients at different stations. Results: Pre- post workshop survey showed increased understanding by the students of the importance of effective communication skills. Results of the paired T-Test revealed an increased awareness of the importance of communication skills among the students with p values<0.001 for all dimensions measured. Conclusion: Students need a strong foundation and an early start to build communication skills..